PENGARUH KERJASAMA TIM, GAYA KEPEMIMPINAN, DAN KOMUNIKASI TERHADAP PRODUKTIVITAS DI NDALEM MANTEN WEDDING ORGANIZER PONOROGO JAWA TIMUR - Prasista, Talitha Ega; Hartono, Sri; Kristiyana, Naning (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to examine the effect of teamwork, leadership style, and communication on productivity at Ndalem Manten Ponorogo, East Java. The sample of this study was employees at Ndalem Manten wedding organizer. The method used in this study is a quantitative method. The data in this study were obtained by distributing questionnaires online to respondents. The population in this study were permanent and freelance employees at Ndalem Manten wedding organizer. The sample in this study was 36 using a purposive sampling technique. The results of this study indicate that employee involvement, teamwork, and selection of freelance workers have a positive and significant effect on productivity at Ndalem Manten Wedding Organizer Ponorogo.